RESISTÊNCIA DE CULTIVARES DE ALGODOEIRO A Spodoptera frugiperda (J.E. SMITH, 1797) (LEPIDOPTERA: NOCTUIDAE) - Moreno, Diego Boareto; Boiça Junior, Arlindo Leal; Jesus, Flávio Gonçalves de; Janini, Júlio Cesar (REVISTA DE AGRICULTURA, 2015)
RESISTÊNCIA DE CULTIVARES DE ALGODOEIRO A Spodoptera frugiperda (J.E. SMITH, 1797) (LEPIDOPTERA: NOCTUIDAE)